Aerospace series. Steel X3CrNiMoAl13-8-2 (1.4534). Solution annealed and precipitation hardened. 1 400 ≤ Rm ≤ 1 550 MPa. Forgings. De ≤ 100 mm. (17th December 2019) - British Standards Institution
No abstract available